Cascade‐Amplifying Synergistic Therapy for Intracranial Glioma via Endogenous Reactive Oxygen Species‐Triggered "All‐in‐One" Nanoplatform. (9th September 2021) - Wu, Pengying; Zhu, Mingting; Li, Yan; Ya, Zhen; Yang, Yabo; Yuan, Yuchen; Dong, Wei; Guo, Shifang; Lu, Shukuan; Zhang, Lei; Zong, Yujin; Wan, Mingxi
Abstract: Targeted delivery of drug‐loaded nanoparticles to brain tumors is exceptionally difficult due to the blood‐brain barrier (BBB). In addition, several chemotherapeutic drugs induce autophagy, which protects the cells from apoptosis and mitigates the therapeutic effect. A novel "all‐in‐one" nanoparticles (AMPTL) consisting of endogenous reactive oxygen species‐cleavable thioketal linkers conjugated to paclitaxel (PTX) and autophagy inhibitor 3‐methyladenine, and angiopep‐2 peptide‐modified DSPE‐PEG2K is developed. AMPTL inhibits autophagy in the C6 glioma cells, as indicated by fewer autophagic vesicles, lower LC3‐II expression and accumulation of SQSTM1/P62, and significantly upregulates p53 and the pro‐apoptotic Bax and cleaved caspase‐3 proteins. In addition, AMPTL treatment induces cell cycle arrest at the G2/M phase. Thus, inhibition of autophagy in the AMPTL‐treated glioma cells sensitizes them to PTX‐induced cell cycle arrest and apoptosis. Furthermore, focused pulse ultrasound and microbubbles enhances the delivery of AMPTL to intracranial glioma tissues by reversibly opening the BBB, which significantly inhibits xenograft growth and markedly improves survival rates of the tumor‐bearing mice. Taken together, combining non‐invasive BBB opening with autophagy inhibitors and chemotherapeutic drugs can achieve cascade‐amplifying synergistic therapeutic effects against glioma. Abstract : In this study, a versatile intelligent endogenous reactive oxygen species‐triggered nanoplatform combined with controllable opening and recovery of the blood‐brain barrier for synergistic brain tumor therapy via inhibition autophagy is reported. These findings provide potential advanced knowledge of nanocarriers for clinical applications.